The first successful pediatric heart transplant and results from the earliest era. (1st January 2019) - Kirk, Richard; Butts, Ryan J.; Dipchand, Anne I.
Abstract: Background: The first pediatric heart transplant died 5 hours after transplant and the case was published by Kantrowitz. There is no report of the first successful case in the medical literature, nor indeed the outcome of children transplanted prior to 1982. However, we recently discovered that children from this period were entered retrospectively into the ISHLT Registry when it began and they form the basis of this report. Methods: A retrospective review of the ISHLT Thoracic Registry was undertaken for pediatric heart transplants prior to 1982. Demographic and descriptive data, and patient and graft survival were analyzed. Results: Thirty children (24 male) had a median age of 13 years (IQR 12‐16) at the time of primary transplant. The underlying cardiac diagnosis was cardiomyopathy (18), congenital heart disease (7), not reported (5). The median follow‐up was 2.63 years (IQR 0.1‐7.2). Twenty‐two patients are known to have died, and eight underwent retransplantation. Median patient survival was 3.5 years. The first patient to survive for more than one year was transplanted in 1968 and survived 6 years. Conclusion: The definition of a successful transplant is debatable; however, the first child reported to the registry to survive beyond one year was transplanted in 1968. Survival for these early patients was considerably less than the subsequent eras and retransplantation more common; however, the experience in managing these children laid the foundation for the future.